Efeitos da terapia a laser associada ou não ao plasma rico em plaquetas na reparação do tecido muscular de ratos - Ozaki, Guilherme Akio Tamura [UNESP] (2015)
Treatment of muscle injuries usually results in the interruption of sports practice, so studies aimed at anticipating the return to activity, with proper tissue repair become important. Therefore, this study intended to evaluate the effect of low level laser therapy (LLLT) associated or not with platelet-rich plasma (PRP) in the treatment of muscle injury. Forty two animals were used divided into six groups (n=7), Control (C), Acute Injury Control (CLA), Injury Control (CL), Injury LLLT (LLT), injury PRP (LP), and injury LLLT and PRP (LLtP). Muscle injury were induced by stretching the gastrocnemius muscle and the animals of groups LLtP and LP received the application of PRP immediately after the injury. The LLLT were applied daily for seven days. The animals were euthanized seven days after the injury, except the CLA group, which were euthanized 48 hours after injury. Histological slides of the gastrocnemius muscle were prepared without stained for Raman analyze and stained by Hematoxylin and eosin (HE), and Picrosirius witch are analyzed by fractal dimension (DF), analyzing the inflammatory infiltrated and collagen. Analysis of NADH and NAD were performed by Raman spectroscopy...